The National Ethical Guideline of Transplantation Research in Iran - F Zahedi; B Larijani; A Parsapoor; M Mohaghegh-Dolatabadi; A Jafarian; SM Kazemeini (Tehran University of Medical Sciences, 2008)
Recent advances in organ transplantation have promised certain benefits to humankind. Consequently, it is neces¬sary to take into consideration all aspects of these new approaches and provide specific ethical guidelines for re¬search in this field. Con¬sidering the ever-increasing advancements of transplantation in Iran and noting the necessity of scientific researches in this field, and to observe ethical principles in such researches, compilation of the "Na¬tional Ethical Guidelines for Transplanta¬tion Researches", as one topic of the "Specific National Ethical Guidelines for Biomedical Research" were considered in our coun¬try. We stated some points of this guideline in this article.